A review on potential use of hydrogen in aviation applications. (2016) - Dincer, Ibrahim; Acar, Canan
In this paper, utilisation of hydrogen as an alternative aviation fuel is reviewed, along with some past and present-day activities, covering three critical topics of energy consumption, environmental impact and emission related cost. It also evaluates the energy consumptions, environmental impacts, emission-related costs of jet fuel A, natural gas and hydrogen from selected production methods in short and long distance aircrafts. Furthermore, costs and efficiencies of hydrogen production from steam methane reforming and wind, PV, and hydro-based electrolysis are compared for a more detailed comparative assessment. Aviation fuel evaluation results show that hydrogen from hydro- and wind-based electrolysis is a promising clean, efficient and less costly candidate among the selected fuels in this study. The assessment study shows that compared to selected hydrogen production options, hydro-based electrolysis is the most advantageous one.